Effectiveness of Music and Art Therapy on Hemodynamic Status in Pediatric Cancer Patients Undergoing Chemotherapy - Lomboan, Shania Putri; Simanjuntak, Susi Roida; Gannika, Lenny (Inspirasi Foundation, 2025)
Introduction: Cancer in children is a major global health issue, with over 400,000 new cases annually. Pediatric cancer treatment often results in fatigue and psychological stress, which may influence hemodynamic status such as pulse, blood pressure, respiration, and oxygen saturation. Music and art therapy have emerged as supportive nursing interventions that may help stabilize these indicators. Objective: This study aims to evaluate the effectiveness of combined music and art therapy on the hemodynamic status of pediatric cancer patients undergoing chemotherapy. Method: This study used a descriptive case study design involving three pediatric cancer patients with varying diagnoses: Hodgkin’s lymphoma, rectal adenocarcinoma, and ovarian clear cell carcinoma. The intervention consisted of simultaneous music and art therapy sessions administered for 15–20 minutes daily over three consecutive days. Hemodynamic indicators, including pulse rate, blood pressure, respiration rate, and oxygen saturation, were monitored before and after each session. Result: All three respondents showed a consistent decrease in pulse rate over the three days of therapy, indicating reduced physiological stress. However, changes in other hemodynamic indicators, such as systolic and diastolic blood pressure, respiratory rate, andoxygen saturation, were inconsistent across the participants. Despite variability in clinical outcomes, verbal and observational feedback indicated positive emotional responses and improved engagement during therapy. Conclusion: Music and art therapy interventions positively influenced the pulse rate of pediatric cancer patients, suggesting an impact on autonomic nervous system regulation. Although other hemodynamic parameters showed inconsistent changes, the interventions contributed to psychological comfort and may enhance the overall well-being of pediatric oncology patients. Further research with larger samples and extended intervention durations is recommended to confirm clinical significance.